Driver Safety System using Arduino - Shiny, G. Susan; Rajalakshmi, G.; Kamalambika, K.; Kavitha, P.; Brentha, S. (Journal of Ubiquitous Computing and Communication Technologies, 2023)
The most frequent cause of auto accidents is poor driving. This occurs frequently when a driver is intoxicated or sleepy. Driver fatigue is often acknowledged as a significant factor contributing to collisions as 20% of the accidents occur only due to drowsy driving or tiredness. It is hoped that the technological advancements can at least partially, avoid these thanks to technological improvements. The research put froth utilizes an IR sensor, to measures and regulates eye blinking. The infrared waves that reach the eyes are sent using an IR transmitter. The reflected infrared rays from an eye are picked up by the IR receiver. If the eye is closed, the result is to raise the alarm. Also, the pulse sensor is used to alert people by sending SMS in case of any health issues to the driver. In this study, eye blink of the driver is monitored to prevent accidents during drowsy driving. Here, a single eye blink sensor is installed in a vehicle to alert the driver during fatigue. A Global Positioning System (GPS) is also used in the proposed design to send location alerts.